TERAPI MENULIS EKSPRESIF TERHADAP TINGKAT KECEMASAN PADA ODHA - Ni Made Diah Kartika Sari; I Nengah Sumirta (Jurnal Gema Keperawatan, 2019)
The aim of this study was to determine the effect of expressive writing therapy on anxiety levels in PLWHA at the Denpasar Paramacitta Spirit Foundation. This study used a type of pre-experimental design with the design of one group pretest-posttest. The number of samples in this study were 16 people who were selected by the probability sampling technique type of simple random sampling. The results showed that the level of anxiety before being given expressive writing therapy was mostly in the category of moderate anxiety as many as 15 people (93.75%), after being given expressive writing therapy there was a decrease in anxiety levels to a low category of 12 people (75%). The results of this study were tested by Wilcoxon statistical test, obtained results (p) = 0.001 (p 0.05).